2020
DOI: 10.1177/0020294019887194
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of rapid prototyping technology for the fabrication of an orthopedic shoe inserts for foot pain reprieve using thermo-softening viscoelastic polymers: A novel experimental approach

Abstract: This research work has been completed by concentrating on the structure of inserts for foot orthosis fabricated by utilizing rapid prototyping technology. Thermoplastic elastomer and thermoplastic polyurethane are the most commonly used materials that are being used in customized three-dimensional printed orthotic insoles, which are comfortable and prevent the user in many foot disorders. Thermo-softening viscoelastic polymers, explicitly Filaflex and Ninjaflex, have been printed by utilizing Flash Forge three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Utilization with biocompatible polymers minimizes a drug’s adverse effects and negative consequences. Biopolymers, including biodegradable biopolymers, do not have a persistent inflammatory influence, and are characterized by high porosity and permeability, and outstanding therapeutic properties [ 369 , 370 , 371 ].…”
Section: Resultsmentioning
confidence: 99%
“…Utilization with biocompatible polymers minimizes a drug’s adverse effects and negative consequences. Biopolymers, including biodegradable biopolymers, do not have a persistent inflammatory influence, and are characterized by high porosity and permeability, and outstanding therapeutic properties [ 369 , 370 , 371 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, at higher natural fiber loading (15 wt% jute and grewia), the improvement in the erosive wear was not significant as obtained in the study. Apparently, the erosive wear examination revealed that main wear mechanism responsible for material removal is groove formation and micro-ploughing [ 63 , 64 , 65 ]. A close examination also discloses brittle fractures at some parts, which shows that a small amount of impact forces was also acting on the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Conducting polymers also find applications in tissue engineering due to their stimulusresponsive property. The composites of these polymers act as substrates that promote cell growth, adhesion, and proliferation at the polymer-tissue interface [130,131,[145][146][147][148][149][150][151][152][153][154][155][156][157][158].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…The graphene nanohybrid of these polymers is used as an electrode in synthesis of capacitors. These nanohybrid materials increase stability, flexibility, and capacity of capacitors [149][150][151][152][153][154][155][156][157][158][159][160][161]. The different properties of polymers like thermal stability, mechanical properties, conductivity, corrosion protection properties on steel and aluminium can be escalated to a firm extent by doping.…”
Section: Diabetic Monitoringmentioning
confidence: 99%